2015
DOI: 10.1016/j.cell.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

FOXG1-Dependent Dysregulation of GABA/Glutamate Neuron Differentiation in Autism Spectrum Disorders

Abstract: SUMMARY Autism spectrum disorder (ASD) is a disorder of brain development. Most cases lack a clear etiology or genetic basis, and the difficulty of reenacting human brain development has precluded understanding of ASD pathophysiology. Here we use three-dimensional neural cultures (organoids) derived from induced pluripotent stem cells (iPSCs) to investigate neurodevelopmental alterations in individuals with severe idiopathic ASD. While no known underlying genomic mutation could be identified, transcriptome and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
906
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 963 publications
(1,002 citation statements)
references
References 54 publications
47
906
3
8
Order By: Relevance
“…Importantly, we found that the morphology and sizes of ventricular zones of these iPS‐derived organoids, the region of our interest, were fairly consistent between organoids as was also demonstrated recently using iPS‐derived organoids (Mariani et al , 2015). While we observed proliferating RGs on the apical side toward the lumen, we observed neuronal cells exhibiting neuronal proteins such as doublecortin (DCX) and TUJ1 at the basal side away from the lumen (Fig 6A and B, Appendix Figs S9C and S10).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Importantly, we found that the morphology and sizes of ventricular zones of these iPS‐derived organoids, the region of our interest, were fairly consistent between organoids as was also demonstrated recently using iPS‐derived organoids (Mariani et al , 2015). While we observed proliferating RGs on the apical side toward the lumen, we observed neuronal cells exhibiting neuronal proteins such as doublecortin (DCX) and TUJ1 at the basal side away from the lumen (Fig 6A and B, Appendix Figs S9C and S10).…”
Section: Resultssupporting
confidence: 85%
“…To determine whether aberrant CDC function could lead to brain defects, we adopted the recently described three‐dimensional culture system to generate organoids in vitro (Lancaster et al , 2013; Mariani et al , 2015). Starting with the same number of WT and Seckel iPS cells, matrigel‐embedded droplets of neural epithelium were grown in spinner bioreactors (Appendix Fig S9A).…”
Section: Resultsmentioning
confidence: 99%
“…The observations of a cortical architecture and cellular behavior based largely on marker gene expression are generally consistent with in vivo patterns of human fetal cortical development. Bulk transcriptome analysis has provided a genome-wide perspective of the gene expression landscape in whole organoids (12). However, due to heterogeneity within cerebral organoids, bulk methods obscure cell-type diversity and provide coarse insight into organoid neurogenic programs.…”
Section: Significancementioning
confidence: 99%
“…Consistent with that notion, improved uniformity is seen in the region‐specific organoid models which employ soluble neural inductive factors, but still there exist considerable variabilities 30, 31, 35. At least three reasons could account for them.…”
Section: Current Limitations Of Brain Organoidsmentioning
confidence: 71%
“…Building on these earlier works, a recent flurry of papers described the generation of various neural organoids (Table 1), ranging from the whole‐brain organoids,27, 28, 29 to large sub‐brain regions such as cortical organoids,30, 31 to specific regions, including cerebellum,32 midbrain,33 adenohypophysis,34 hypothalamus,35 and hippocampus 36. Comparing with the classical neurospheres, these organoids are generally much larger.…”
Section: Brain Organoids: Current Technologiesmentioning
confidence: 99%